The Effect of Calorie Labels on Caloric Intake and Restaurant Revenue: Evidence from Two Full-Service Restaurants. (May 2014) - Ellison, Brenna; Lusk, Jayson L.; Davis, David
Abstract : Field experiment data were used to study the effect of numeric calorie labels in two full-service restaurants. Ultimately, both field experiments, despite using different experimental designs, reached the same conclusion: the numeric calorie label had no significant effect on total caloric intake. However, results revealed the addition of a traffic light symbol to the numeric label led to a 67.8-kcal reduction in average calories ordered. Furthermore, results showed restaurant revenue is unlikely to be affected by the addition of calorie labels on menus. The results have implications for restaurant labeling laws that are being considered around the world.